Statistically Left Outs and Socio-Historically Legitimized Groups in Nepal - Chaudhary, Nathuram (Far Western Review, 2023)
This article explores the realities underpinning the statistically left outs and socio-historically legitimized groups in Nepal by relating the Vedic and Western theoretical perspectives to perceive the reality at the grassroots level. It does so by summarizing the Vedic perspectives and various sociological theories and then looking at the local issues linking with the Western perspectives with my reflection. It reveals that experiential knowledge, globalization, and legitimization are the major sociological aspects influencing the Structure of Nepalese society. The article concludes that the ruling class prepares Statistical data for their purpose, which leaves out the actual/accurate data about the subaltern, ethnic, and minority groups. Voices of the poor students, girls, ethnic and minority group of the School can be addressed by making the policy in education and transforming the school structure with inclusive pedagogy into equity and equality social environment for the students is the major implication of this article.